2019
DOI: 10.1016/j.heliyon.2019.e02821
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of chicken nail extracts as corrosion inhibitor on mild steel in 2M H2SO4

Abstract: The inhibiting effects of Chicken Nails Extract (CNE) on Mild Steel corrosion in 2M H2SO4 were investigated in this study. The effect of the concentration of inhibitor (0.5–1.5 g/l), time (5–8 h) and temperature (40-70oc) on Inhibition efficiency were investigated using Response Surface Methodology. The Physiochemical analysis and proximate analysis of the CNE were investigated; the result showed that organic constituents were present which made the Chicken nails extract a good inhibitor. The rate of corrosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…This showed that the experimental data obtained for the Inhibition Efficiency are statistically consistent and the second order polynomial model selected was suitable for modelling the second-order polynomial equation in final equation terms of the coded values of the process parameters as showed above. This agrees with the work of [16]. Table 6 and Fig.…”
Section: Optimization Of the Inhibition Process Using Response Surface Methodology (Rsm)supporting
confidence: 93%
See 1 more Smart Citation
“…This showed that the experimental data obtained for the Inhibition Efficiency are statistically consistent and the second order polynomial model selected was suitable for modelling the second-order polynomial equation in final equation terms of the coded values of the process parameters as showed above. This agrees with the work of [16]. Table 6 and Fig.…”
Section: Optimization Of the Inhibition Process Using Response Surface Methodology (Rsm)supporting
confidence: 93%
“…Weight loss measurement was conducted under total immersion using a 250ml beaker containing prepared solution at a temperature range of 30℃ to 50℃ which was placed in a thermostatregulated water bath, a method adopted by [16] in his study.…”
Section: Weight Loss Measurementmentioning
confidence: 99%
“…It was observed from Figure 4(a) that the blank coupon was highly corroded with cracks, futher more, it was observed from Figure 4(b) (best level) gotten from experimental design that there were formation of plain layer with protective film which was as a result of the protective layer formed by the extract, while in Figure 4(c) optimal level that was validated showed more protective film was formed, which can be attributed to adsorption. This result was supported by (Olawale et al, 2019) findings on the inhibiting effects of Chicken Nails Extract (CNE) on mild steel corrosion in 2M H 2 SO 4 , as well as Anadebe et al (2018) findings on mild steel corrosion in acid medium with bitter kola leaf extract as an inhibitor and Anadebe et al (2019) findings on the application of pigeon pea leaf (PPL) extract as an anti-corrosion agent for mild steel.in acid environment (HCl solution).…”
Section: Scanning Electron Microscopymentioning
confidence: 59%
“…It can be concluded that SVSE contains some unique functional groups. The empty orbitals of these organic functional groups can effectively adsorb onto the surface of CS, ultimately slowing down its corrosion [48].…”
Section: Ftir Analysismentioning
confidence: 99%